Kahoot! as a Digital Tool to Enhance Student Motivation and Academic Outcomes in Music Arts Classes - Awaluddin Muin; Nurhikmah H; Lu’mu; Abdul Malik Ramli; Hikmawati Usman (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Digital tools such as Kahoot! are widely recognized as effective means of increasing students’ engagement in learning activities. However, their use is often limited to enhancing classroom enjoyment rather than being evaluated for their pedagogical impact. This study aims to evaluate the effect of Kahoot! as a digital learning tool on students’ motivation and learning outcomes in Music Education. This research employed a pre-experimental design involving 29 fifth-grade students. Data were analyzed using both descriptive and inferential statistical methods with the assistance of SPSS version 26. The main findings indicate a statistically significant relationship between the use of Kahoot! and students’ learning motivation. The integration of Kahoot! in the classroom increased students’ interest and enthusiasm, creating a more enjoyable learning environment and encouraging active participation. The platform also functioned as an engaging, competitive, and collaborative learning medium. The study concludes that the use of Kahoot! has a positive effect on both students’ motivation and learning outcomes in Music Education. This research contributes to educational practice and academic development by demonstrating that game-based digital tools can effectively support learning in arts education. The implications of this study suggest that integrating interactive technology into instruction can serve as an effective strategy to enhance students’ motivation and academic achievement.